Impact of Islamic-Based Services Provided by Lecturers and Staff on Students' Perceptions of Religiosity - Astuti, Mardiah; Ismail, Fajri; Triana, Yunika; Rifa'i, Andi Arif (International Journal of Learning, Teaching and Educational Research, 2024)
This paper aims to determine the relationship between Islamic values of lecturers and academic staff towards student perceptions on religiosity. This paper established a regression equation model between the two and explained the importance of the Islamic values of lecturers and academic staff to improve student religious behavior and attitude. This study used a quantitative survey method in the form of a relationship survey. The total population was 3,194 students at one of the largest State Islamic Universities in Indonesia. The research sample was taken randomly. A sample of 750 respondents was obtained from four study programs. The instrument used was a questionnaire consisting of 24 statements using a Likert scale. The results of the study showed that the Islamic-based and the dimensional aspect (Islamic values) of lecturers and academic staff services, had a significant effects on student perceptions. The conclusion drawn was that the dimensions of the Islamic values of lecturers and academic staff had a significant effect on positive perception aspects. The implication of practice or policy is that policy makers are required to improve Islamic-based academic and non-academic services in order to change the character and increase the positive perspective of students. https://doi.org/10.26803/ijlter.23.4.8